Effect of Selected Polysaccharides on Physical Properties of Fish Gelatin-Based Edible Film - Mohammad Zadeh, Elham (2011)
Gelatin-based edible packaging is thin, flexible and biodegradable bio polymers with broad applications. However, physical and thermal properties of fish gelatin limit its use in many applications. Therefore, the objective of this study was to improve the mechanical properties, permeability properties including water vapor (WVP) and oxygen permeability (PO ), thermal properties and the color properties of the fish gelatin-based film by the addition of gellan and К-carrageenan as variables with sorbitol in different concentrations. The study also aimed to identify the best combination of the additives that could produce an edible fish gelatin-based film having improved physical properties. Fish gelatin-based film was prepared by casting technique with the average thickness of 0.05±0.01mm. Control film was 5% fish gelatin with no gellan, К-carrageenan and sorbitol. Different levels of gellan and К-carrageenan with 25% and 35% sorbitol had significant effects on TS, %E, PF, WVP, PO2, Tm and the enthalpy (p<0.05). The addition of К-carrageenan (0-2% w/w based on gelatin) or gellan (0-2% w/w based on gelatin) with sorbitol (25% and 35% w/w based on gelatin) improved mechanical, permeability and thermal properties of fish gelatin-based film compared to control film or those films with just sorbitol. Formulated films contain 35% sorbitol and 2% gellan showed the highest %E and PD among the films contain gellan, also melting temperature and the enthalpy of these films increased to 140°C and 53J/s respectively. Water vapor and oxygen permeability were decreased after adding gellan and sorbitol, although they had no significant effect on TS and PF as compared to control film. Formulated films with 25% sorbitol and 2% К-carrageenan had the highest TS and PF. The films containing 35% sorbitol and 2% К-carrageenan showed the highest PD, E and thermal properties, which were around 95.88%, 130% and also Tm and ΔHm around 142.5 °C and 131.4 J/g respectively. The addition of К-carrageenan and sorbitol improved the WVP and PO2 as compared with control film. К-carrageenan had more positive effect on the physical properties of formulated fish gelatin film rather than gellan. Formulated films with 2% К-carrageenan and 35% sorbitol had better mechanical, thermal and permeability properties of the film. The brightness of the formulated films was decreased and the yellowness and greenness were increased after adding either gellan or К-carrageenan. The comparison of the best level of formulated gelatin film with PLA film showed that formulated gelatin film had better elasticity and permeability properties and lower strength than PLA film.